Modelling and Simulation of a Fluidized Bed Reactor for Minimum Ammonium Nitrate and Reduction of NOx Emissions (Chemical Engineering Research Bulletin, 2018)
Due to the environmental legislations related to the nitrates and their emissions, thermal decomposition of ammonium nitrate (AN) in a fluidized reactor (FR) is regarded one of the most reasonable chemical-free disposal process for an aqueous waste nitrate stream. Therefore, the present study is aimed to improve a mathematical model based on experiments (from the literature) for enhancing the design of such reactor in an environmentally friendly manner. Where, the optimal kinetic parameters of the relevant reactions are firstly obtained employing the optimization technique keeping in mind the goal to construct the model with high exactness. Such design factors are then utilized for the purpose of getting the optimal operating conditions of fluidized bed reactor (FBR) achieving the main target of this process with ammonium nitrate-free content (Nil) at the end of the reactor in addition to reducing the NOx emissions. The model is based on the two-phase theory of a FBR with predicting the concentration behavior along the reaction zone length for all components in the emulsion and bubble phases in addition to the temperature profile of the gas phase. New results related to output conversion of ammonium nitrate as well as NO content at the optimal operating conditions has been obtained in comparison with those reported in the literature.Chemical Engineering Research Bulletin 20(2018) 8-18